2019
DOI: 10.1038/s41467-019-10009-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of pore formation during laser powder bed fusion additive manufacturing

Abstract: Laser powder bed fusion additive manufacturing is an emerging 3D printing technique for the fabrication of advanced metal components. Widespread adoption of it and similar additive technologies is hampered by poor understanding of laser-metal interactions under such extreme thermal regimes. Here, we elucidate the mechanism of pore formation and liquid-solid interface dynamics during typical laser powder bed fusion conditions using in situ X-ray imaging and multi-physics simulations. Pores are revealed to form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
178
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 508 publications
(194 citation statements)
references
References 43 publications
8
178
0
8
Order By: Relevance
“…In our experimental condition, the pores could not travel far away from the fluctuating keyhole channel and, therefore, were prone to merging with the channel. Another typically reported source of porosity is by the fast collapse of the keyhole channel at the end of the process, which often leads to vapor being trapped in the melt pool and forming pores 11,48,49 . This phenomenon was also observed in our work and can be seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our experimental condition, the pores could not travel far away from the fluctuating keyhole channel and, therefore, were prone to merging with the channel. Another typically reported source of porosity is by the fast collapse of the keyhole channel at the end of the process, which often leads to vapor being trapped in the melt pool and forming pores 11,48,49 . This phenomenon was also observed in our work and can be seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An excessive energy input process region was not determined but experimentation at higher levels of energy density will probably yield greater porosity caused by gas entrapment due to the keyhole formation. This type of defect formation at elevated energy densities levels has been previously denoted by Cunnigham et al [40] through x-ray microtomographies and by Martin et al [41] by means of high speed synchrotron x-ray imaging. Microhardness measurements are reported in figure 11 as a function of energy density.…”
Section: Resultsmentioning
confidence: 73%
“…This data correlates with the smallest porosity percentage of 0.07 %. Martin et al [19] demonstrated that the laser turn forms the major pores value. This explains the low porosity for the "Line" scan strategy.…”
Section: Scan Strategymentioning
confidence: 99%